Temporal Web Dynamics And Its Application To Information Retrieval - Chang, Yi; Diaz, Fernando; Dong, Anlei; Dumais, Susan; Radinsky, Kira; Shokouhi, Milad (Proceedings of WSDM 2013 (Tutorial), 2013)
The World Wide Web is highly dynamic and is constantly evolving to cover the latest information about the physical and social updates in the world. At the same time, the changes in web contents are entangled with new information needs and time-sensitive user interactions with information sources. To address these temporal information needs effectively, it is essential for the search engines to model web dynamics and understand the changes in user behavior over time that are caused by them. In this full-day tutorial, we focus on modeling time-sensitive content on the web, and discuss the state-of-the-art approaches for integrating temporal signals in web search. We address many of the related research topics including those associated with searching dynamic collections, defining time-sensitive relevance, understanding user query behavior over time, and investigating the mains reasons behind content changes. We also cover algorithms, architectures, evaluation methodologies and metrics for time-aware search, and discuss the latest breakthroughs and open challenges, both from the algorithmic and the architectural perspectives.